Digital Marketing Strategies for Sustainable Brand Development - Azhar, Noviridhany Maulana (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research investigates the relationship between digital marketing strategies and sustainable brand development. Using a systematic literature review, we analyze various factors influencing brand development in a digital context. Our findings show that significant investment in digital marketing, high quality digital content, ongoing interactions with customers through digital channels, and consistency and relevance of digital marketing messages have a major impact on sustainable brand development. This emphasizes the importance of a targeted and effective digital marketing strategy in achieving sustainable brand development goals in this digital era.